Impact of LX4211 on Cardiovascular Risk Factors in Type 2 Diabetes - Vinall, Phil (MD Conference Express, 2012)
LX4211, a dual inhibitor of sodium glucose transporters 1 and 2 (SGLT1/2), demonstrated a clear dose reduction in plasma glucose concentration (HbA1C) in patients with type 2 diabetes mellitus (T2DM) inadequately controlled on metformin monotherapy in the Safety and Efficacy of LX4211 with Metformin in T2DM Patients with Inadequate Glycemic Control on Metformin study. SGLT1 is primarily responsible for gastrointestinal glucose absorption, while SGLT2 is primarily responsible for renal glucose reabsorption, leading to reductions in blood glucose levels and weight loss.